2022
DOI: 10.14202/vetworld.2022.2535-2542
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and multidrug resistance of Enterococcus species isolated from chickens at slaughterhouses in Nakhon Ratchasima Province, Thailand

Abstract: Background and Aim: Enterococcus is a commensal bacteria found in humans and animals, which can cause human nosocomial infections. One of the most contaminated enterococcal sources is poultry meat. Therefore, this study estimated the prevalence and antimicrobial resistance (AMR) profile of Enterococcus from chickens and their meat products at local slaughterhouses in Nakhon Ratchasima Province, Thailand. Materials and Methods: From January 2021 to March 2022, 558 samples from 279 cloacal swabs and breast meat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
1
1
Order By: Relevance
“…It is unequivocal that the prevalence of distinct species of enterococci, along with their levels of antimicrobial resistance and multiresistance, tends to correlate with the specific type of material and the kind of animals from which the strains are isolated [36][37][38][39][40]. In our study, the enterococci prevalence of 27.6% in one-day-old chickens is comparable to prior reports of 29.75% and 28.32% in broiler chickens [41] but remains relatively low when compared to the prevalence in wild animals [38]. This observed pattern could be influenced by various factors, including geographical and climatic regions, economic statuses, regional legislations, animal husbandry practices, and the rational utilization of antimicrobials, which manifests in the form of antimicrobial resistance in the captured strains [11,40,[42][43][44].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It is unequivocal that the prevalence of distinct species of enterococci, along with their levels of antimicrobial resistance and multiresistance, tends to correlate with the specific type of material and the kind of animals from which the strains are isolated [36][37][38][39][40]. In our study, the enterococci prevalence of 27.6% in one-day-old chickens is comparable to prior reports of 29.75% and 28.32% in broiler chickens [41] but remains relatively low when compared to the prevalence in wild animals [38]. This observed pattern could be influenced by various factors, including geographical and climatic regions, economic statuses, regional legislations, animal husbandry practices, and the rational utilization of antimicrobials, which manifests in the form of antimicrobial resistance in the captured strains [11,40,[42][43][44].…”
Section: Discussionsupporting
confidence: 84%
“…Some enterococci also act as opportunistic pathogens in birds. In Thailand in 2022, different species of enterococci were detected in cloacal swabs and chicken meat in 29.75% and 28.32% of cases, respectively [41]. In avian pathology, the most significant species are E. faecalis, Enterococcus cecorum, E. hirae, and E. durans.…”
Section: Discussionmentioning
confidence: 99%
“…Another previous study [ 30 ] also reported a higher prevalence than that reported in the present study. Conversely, the prevalence rate in our study was higher than the rates reported in Ethiopia [ 31 ], Pakistan [ 32 ] and Thailand [ 33 ]. The differences in the isolation rates of Enterococci can be attributed to several factors, including antibiotic use, environmental factors and methodology.…”
Section: Discussioncontrasting
confidence: 97%
“…In addition, if antibiotic-resistant bacteria in the human body lead to infection and spread to other people, public health problems may occur. As a result, the treatment and healing process with certain antibiotics becomes ineffective [8].…”
Section: Introductionmentioning
confidence: 99%